Overview of Online Halal Certification: Practice and Issues - Nurdinah Abu Bakar, Sazelin Arif, S. Safiah Sidek (International Journal of Advanced Science and Technology, 2020)
The good value brought by having “halal” certificate has made the demand for halal application increased. To cater with the demand and fastened the process, an online halal certification application system named MYeHalal system has been introduced firstly on 2007. However, some halal applicants’ were having difficulties in using the system and end up using the halal consultation agency services to complete their halal certification application which caused them to spend the unnecessary costs. This paper reviews 10 years most current studies that discussing on the practice and process of applying halal online and its related inefficiencies issues. It was found that MYehalal system acts more than online form and it requires halal applicants to be prepared in terms of documentations, ingredients’ information and other related rules or procedures implied. Operational inefficiencies, applicants’ inefficiencies and technical inefficiencies were the 3 inefficiencies found that hindering the successful usage of the system. This will be the preliminary study of the proposed future study to connect the technical and non-technical elements in online halal certification application as it may give the holistic view and nuanced understanding on the usage of the MYeHalal system.